2013
DOI: 10.1371/journal.pone.0082604
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/Aglycemia-Induced Endothelial Barrier Dysfunction and Tight Junction Protein Downregulation Can Be Ameliorated by Citicoline

Abstract: This study explores the effect of citicoline on the permeability and expression of tight junction proteins (TJPs) in endothelial cells under hypoxia/aglycemia conditions. Hypoxia or oxygen and glucose deprivation (OGD) was utilized to induce endothelial barrier breakdown model on human umbilical vein endothelial cells (HUVECs) and mouse brain microvascular endothelial cells (bEnd.3s). The effect of citicoline on endothelial barrier breakdown models was determined at either low or high concentrations. FITC-Dext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Cells were placed on the upper side of the insert and allowed to grow to confluence. FITC-dextran at a concentration of 1 mg/ml was added to the endothelial monolayer after exposure to OGD [27]. Two hours later, relative fluorescence passed through the chamber was determined using a fluorescence plate reader at an excitation wavelength at 493 nm and an emission wavelength at 517 nm (SpectraMax M2e; Molecular Devices, Sunnyvale, CA, USA).…”
Section: Hbmec Monolayer Permeability Assaymentioning
confidence: 99%
“…Cells were placed on the upper side of the insert and allowed to grow to confluence. FITC-dextran at a concentration of 1 mg/ml was added to the endothelial monolayer after exposure to OGD [27]. Two hours later, relative fluorescence passed through the chamber was determined using a fluorescence plate reader at an excitation wavelength at 493 nm and an emission wavelength at 517 nm (SpectraMax M2e; Molecular Devices, Sunnyvale, CA, USA).…”
Section: Hbmec Monolayer Permeability Assaymentioning
confidence: 99%
“…Endothelial cells, barrier between tissues and blood, are sensitive to oxygen partial pressure changes in blood [20]. Studies have shown that increasing oxygen partial pressure will enhance endothelial ROS generation and induce a variety of growth factors exerting There is no comparability between the relative levels of DHE and Mito-SOX groups.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hypoxia could disrupt the barrier function of neural blood vessels, and significantly suppress the expression of cldn-5 (Koto et al, 2007;Ma et al, 2013). Studies on blood-brain barrier (BBB) showed that cldn-1 was up-regulated under hypoxia conditions, which had a protective effect against hypoxia-induced increase in blood-brain barrier permeability (Brown et al, 2003).…”
Section: Discussionmentioning
confidence: 99%